An investigation into biochar, acid-modified biochar, and wood vinegar on the remediation of saline−alkali soil and the growth of strawberries - Pan, Xin; Shi, Mei; Chen, Xichao; Kuang, Shaoping; Ullah, Habib; Lu, Hongxiu; Riaz, Luqman (Frontiers in Environmental Science, 2022)
The salinization of several hundred million hectares of land poses a serious threat to global food security and biodiversity. Biochar and wood vinegar amendment has been suggested as a possible way to promote plant productivity and improve soil qualities, whereas less emphasis has been placed on the application of biochar in saline−alkaline soils to increase plant productivity. Herein, the single and composite application of sawdust biochar, wood vinegar, and acid-modified biochar on the restoration of coastal saline−alkali soil and plant growth of strawberry seedlings was investigated. Proximate and ultimate analyses and different characterization techniques such as FTIR and scanning electron microscopy were applied to study the physicochemical characteristics of raw and modified biochar. A pot experiment was conducted to explore the effects of different soil additives on soil properties and strawberry growth. Our results revealed that acid-modified biochar shows the most significant promoting effect on strawberry growth, which could increase the weight gain rate, root length, root specific surface area, and root volume of strawberry seedlings by 41.2%, 18.9%, 23.0%, and 34.7%, respectively. Moreover, the application of acid-modified biochar can effectively alleviate soil salinization by reducing soil pH (7.65) and CEC (19.5 cmol/kg). Furthermore, the addition of biochar can significantly improve the community structure of microorganisms (Proteobacteria) and increase the content of bacteria related to soil nutrient cycling (Pseudomonadaceae and Sphingomonadaceae). Preliminary findings from this study suggested that acid-modified biochar is a potentially effective means of preventing soil salinization and increasing economic crop yields.